Autism: Where the Little Things are Never Little (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this write up is to furnish nearly all elemental aspects on varied behavioral patterns along withdifferent management strategies which may lead to an improvement in treatment planning and managementby the dental practitioners, and comprehensive oral health care of the children suffering from Autism. Alongwith it, this article focuses on raising concerns among primary health care providers and parents of thosechildren regarding there un-mate dental needs.
Keywords: Autism, behavioral pattern, health care providers.